Bond stress-slip model for rebar-concrete interface under monotonic and cyclic loading. (December 2021) - Lv, Xiaoyong; Yu, Zhiwu; Shan, Zhi
Abstract: The mechanical properties of reinforced concrete (RC) structures are closely related to the bond stress-slip relationship of rebar-concrete interface. In this paper, a novel bond stress-slip model under monotonic and cyclic loading is proposed. For interfacial behaviour under monotonic loading, an innovative micro-element model, consisting of a spring element, a friction element and a switch element, is proposed to effectively characterize the interfacial micro-damage mechanical behaviours in a physical sense. By adopting a parallel system of micro-elements and setting the fracture threshold of individual spring element as a random variable, the expressions of the bond stress-slip relationship and interfacial damage variable are derived. Subsequently, succinct practical expressions for the bond strength, peak slip under monotonic loading are formulated. The bond stress-slip model for rebar-concrete interface under monotonic loading are further established. For cyclic constitutive model of rebar-concrete interface, a new method of cyclic correction factor for the degradation law of bond strength is developed. The bond strength degradation under cyclic loading affected by the number of cycles, maximum slip value and opposite loading can be reflected with reasonable accuracy. Furthermore, the predictions calculated by the proposed model under monotonic and cyclic loading are in favorable agreement with experimental results. All parameters in the model have clear physical meaning.